Labour Turnover in Apparel Retail Chains in China - Ming, Xu; Zivlak, Nikola; Ljubičić, Marko (International Journal of Industrial Engineering and Management, 2012)
The purpose of this paper is to provide an overview on consumption and retail sector in China, with focus on leisure clothing retail chains. The problem more specifically addressed in this paper is employee high turnover rate, which directly negatively influences customer experience while shopping, sales performance, as well as brand image of the retailer. During the course of four months, we have visited numerous retail outlets of four major brands, in six major Chinese cities. The study mainly focuses on the relationship between salary level and employee turnover within the given industry. Article history: Received (17 December 2011); Revised (14 January 2012); Accepted (26 January 2012)